MODEL PEMBELAJARAN PAI BERBASIS MULTIKULTURAL DALAM MEWUJUDKAN MODERASI BERAGAMA DIKALANGAN MAHASISWA FAKULTAS EKONOMI UNSOED PURWOKERTO - Sulaiman Sulaiman; M. Misbah (MUADDIB Jurnal Kependidikan dan Keislaman, 2021)
This study has a purpose, namely to determine the learning model of Islamic religious education based on multiculturalism to realize religious moderation among students of the Faculty of Economics and Business, General Sudirman University, Purwokerto. Then the research method used by researchers is descriptive method. In this method, all events or symptoms and descriptions that exist at the location are collected through interviews with resource persons, namely lecturers of Islamic religious education and then the data is analyzed. The data analysis technique used by the researcher is a flow model which includes data reduction, then draws conclusions. In this activity, the research has obtained data directly from sources through Islamic religious education lecturers that: Islamic religious education learning models based on multiculturalism to realize religious moderation among students of the economics and business faculty of Jenderal Soedirman University Purwokerto are andragogy learning strategies, case based learning (CBL), problem solving learning. Where this learning is carried out by adults, then there is one student who comes forward to explain the material to be discussed together, if the discussion causes a dispute or difference of opinion in determining an answer then all of the students' friends are looking for the best way.